Impact of State Laws Governing Physical Education on Attendance Among US High School Students, 2003 to 2017. Issue 8 (November 2019) - An, Ruopeng; Ji, Mengmeng; Clarke, Caitlin; Guan, Chenghua
Purpose: This study assessed the influence of state laws governing physical education (PE) on weekly PE class attendance among US high school students. Design: Cross-sectional. Setting: 2003 to 2017 US national Youth Risk Behavior Survey (YRBS). Participants: A total of 533 468 high school students. Measures: Data on state laws governing PE came from National Cancer Institute's Classification of Laws Associated with School Students (CLASS). Eight distinct state PE policies were scored, with higher scores denoting stronger laws. Analysis: Individual-level YRBS data were merged with CLASS data based on students' residential state and survey year. State fixed-effect negative binomial regressions were performed, adjusting for individual-level characteristics and YRBS survey design. Results: A 1-score increase in state laws governing PE class time, staffing for PE, joint use agreement for physical activity, assessment of health-related fitness, and PE curriculum was associated with an increase in weekly PE attendance by 0.30, 0.28, 0.22, 0.20, and 0.13 days ( P < .001), respectively. In contrast, a 1-score increase in state laws governing moderate-to-vigorous-intensity physical activity time in PE, PE proficiency, and recess time was associated with a reduction in weekly PE attendance by 0.25, 0.15, and 0.09 days ( P < .001), respectively. The effects of most state PE policies on PE class attendance were larger among girls than boys. Conclusion: State PE policies differentially impacted US high school students' PE class attendance, with larger effects on female students.